Metagenomic insight to apprehend the fungal communities associated with leaf blight of Welsh onion in Taiwan - Jayasinghe, Himanshi; Chang, Hao-Xun; Knobloch, Stephen; Yang, Shan-Hua; Hendalage, D. P. Bhagya; Ariyawansa, Kahandawa G. S. U.; Liu, Po-Yu; Stadler, Marc; Ariyawansa, Hiran A. (Frontiers in Plant Science, 2024)
Plants are associated with a large diversity of microbes, and these complex plant-associated microbial communities are critical for plant health. Welsh onion (Allium fistulosum L.) is one of the key and oldest vegetable crops cultivated in Taiwan. The leaf of the Welsh onion is one of the famous spices in Taiwanese cuisine, thus, it is crucial to control foliar diseases. In recent years, Welsh onion cultivation in Taiwan has been severely threatened by the occurrence of leaf blight disease, greatly affecting their yield and quality. However, the overall picture of microbiota associated with the Welsh onion plant is still not clear as most of the recent etiological investigations were heavily based on the isolation of microorganisms from diseased plants. Therefore, studying the diversity of fungal communities associated with the leaf blight symptoms of Welsh onion may provide information regarding key taxa possibly involved in the disease. Therefore, this investigation was mainly designed to understand the major fungal communities associated with leaf blight to identify key taxa potentially involved in the disease and further evaluate any shifts in both phyllosphere and rhizosphere mycobiome assembly due to foliar pathogen infection by amplicon sequencing targeting the Internal Transcribed Spacer (ITS) 1 region of rRNA. The alpha and beta-diversity analyses were used to compare the fungal communities and significant fungal groups were recognized based on linear discriminant analyses. Based on the results of relative abundance data and co-occurrence networks in symptomatic plants we revealed that the leaf blight of Welsh onion in Sanxing, Taiwan is a disease complex mainly involving Stemphylium and Colletotrichum taxa. In addition, fungal genera such as Aspergillus, Athelia and Colletotrichum were abundantly found associated with the symptomatic rhizosphere. Alpha-diversity in some fields indicated a significant increase in species richness in the symptomatic phyllosphere compared to the asymptomatic phyllosphere. These results will broaden our knowledge of pathogens of Welsh onion associated with leaf blight symptoms and will assist in developing effective disease management strategies to control the progress of the disease.